2013
DOI: 10.1111/1365-2478.12057
|View full text |Cite
|
Sign up to set email alerts
|

2D common‐offset traveltime based diffraction enhancement and imaging

Abstract: The diffracted energy in a seismic recording contains key information about small‐scale inhomogeneities or discontinuities of the subsurface. Diffractions can therefore lead to high‐resolution imaging of subsurface structures associated with hydrocarbon traps. However, seismic diffracted signals are often much weaker than specular reflections and consequently require enhancement before they can be utilized. In this paper diffractions are enhanced relative to reflections based on two traveltime techniques, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…() showed that the FO CRS method can be used for regularization. By modifying the FO CRS traveltime, Asgedom, Gelius and Tygel () showed that it can be used to separate diffractions and reflections in prestack data.…”
Section: Introductionmentioning
confidence: 99%
“…() showed that the FO CRS method can be used for regularization. By modifying the FO CRS traveltime, Asgedom, Gelius and Tygel () showed that it can be used to separate diffractions and reflections in prestack data.…”
Section: Introductionmentioning
confidence: 99%
“…Yet they carry very diagnostic information about small seam disruptions, such as faults and dykes, which may be hard to see as vertical offsets on conventional reflection sections. Many approaches have been proposed to extract diffractions from reflection seismic data, including: the local slant stack (plane wave decomposition, τ-p transform) (Harlan et al, 1984 andFomel et al, 2007); plane-wave destruction filter (predictive error filter) (Fomel, 2002 andTaner et al, 2006); focusing and defocusing approach (Khaidukov et al, 2004;Berkovitch et al, 2009;Landa et al, 2010); dip angle domain common imaging gathers (Sava and Fomel, 2003;Klokov and Fomel, 2012;Zhang and Zhang, 2014), and common reflection surface (CRS) stack approach (Dell and Gajewski, 2011;Asgedom et al, 2013;Faccipieri et al, 2013).…”
Section: Diffraction Extraction By Maefmentioning
confidence: 99%
“…We observe that the Fresnel zone is "small" for reflections and "large" for diffractions. As shown in Faccipieri et al (2013) and Asgedom et al (2013), the use of "large" (midpoint) apertures of the diffraction moveout can be very effective for imaging diffraction energy.…”
Section: Crs Diffraction Moveoutmentioning
confidence: 99%